Transformational Leadership And Employee Performance: A Literature Review - Udin Udin , Hosam Alden Riyadh; Radyan Dananjoyo (International Journal of Advanced Science and Technology, 2020)
Utilizing qualitative and quantitative methods, research on leadership has primarily examined performance in large companies in developed countries. Especially over recent decades, transformational leadership has been broadly concentrated. For this reason, this research aimed to overlook the connection between transformational leadership and employee performance from the prior empirical literature. A further literature review has been conducted. Thirty-eight articles in English were selected for final analysis, distributed between the years 2010 and 2020. This research revealed that the transformational leadership style is very significant in affecting the creativity and performance of employees and is suitable to identify novel opportunities and to develop competencies in organizations. Transformational leaders increase the confidence and values of employees; as a result, the employee’s outcome is increased beyond their expected level. Intrinsically, job satisfaction is fostered by transformational leadership, given its capacity to grant intellectual stimulation and a feeling of mission. Transformational leaders will, in general, energize and propel their supporters to assume greater liability and self-governance, in this way, improving workers’ feelings of achievement and job satisfaction.